Engineering and social justice : in the university and beyond - Baillie, Caroline; Pawley, Alice; Riley, Donna (Donna M.) (West Lafayette, Ind. : Purdue University Press, 2012)
"An increasing number of researchers and educators in the field of engineering wish to integrate considerations of social justice into their work and practice. In this volume, an international team of authors, from a range of disciplinary backgrounds, invite scholars to think and teach in new ways that acknowledge the social, as well as technical, impact engineering can have on our world and that open possibilities for social justice movements to help shape engineering/technology. The book examines three areas of an engineering academic's professional role: teaching, research, and community engagement. Some of the authors have created classes to help students think through their roles as engineering practitioners in a changing society, and present case studies here. They also explore questions of access to engineering education. Other contributors are focusing their research on improving the lives of the marginalized and powerless. Yet others are engaging local groups and exploring ways in which universities might serve their communities and in which academic institutions can themselves be more socially just. The contributors take a broad social and ecological justice perspective to critique existing practices and explore alternatives. The result is a handbook for all scholars of engineering who think beyond the technical elements of their field, and an essential reader for anyone who believes in the transformative power of the discipline"--Provided by publisher.
Foreword: Reflections on engineering and social justice in teaching, learning, and research / Karl A. Smith -- Introduction: In the university and beyond / Caroline Baillie, Alice L. Pawley, and Donna Riley -- Developing human-centered design practices and perspectives through service-learning / Monica E. Cardella, Carla B. Zoltowski, and William C. Oakes -- An ethnographic study of social justice themes in engineering education / George D. Ricco and Matthew W. Ohland -- What counts as "engineering": toward a redefinition / Alice L. Pawley -- Waste for life: socially just materials research / Caroline Baillie -- Turbulent fluid mechanics, high speed weapons, and the story of the Earth / George Catalano -- Community colleges, engineering, and social justice / Lisa A. McLoughlin -- Low socioeconomic status individuals: an invisible minority in engineering / Michele L Strutz, Marisa K. Orr, and Matthew W. Ohland -- Viewing access and persistence in engineering through a socioeconomic lens / Matthew W. Ohland [and others] -- An alternative tour of Ford Hall: service toward education and transformation / Donna Riley.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Engineering ethics; Engineering -- Social aspects; Engineering -- Study and teaching; Ingénieurs -- Déontologie.; Ingénierie -- Aspect social; Ingénierie -- Étude et enseignement; TECHNOLOGY & ENGINEERING -- Social Aspects; EDUCATION -- Philosophy & Social Aspects; BUSINESS & ECONOMICS -- Business Ethics; EDUCATION -- Research; Engineering ethics; Engineering -- Social aspects; Engineering -- Study and teaching